How did Latinxs near the U.S.-Mexico border fare during the COVID-19 pandemic? A snapshot of anxiety, depression, and posttraumatic stress symptoms - Villalobos, Bianca T.; Hernandez Rodriguez, Juventino (Frontiers in Psychology, 2023)
Introduction: The current study documented levels of anxiety, depression, posttraumatic stress, and COVID-19 fears and impacts among Latinxs living near the U.S.-Mexico border during the COVID-19 pandemic. Method: Participants of this cross-sectional study were 305 Latinx adults living in the Rio Grande Valley (RGV) who completed an online survey between June and November 2020. Results: About half of participants scored above the cut-off for anxiety (50.2%; GAD-7 scores ≥ 10) and depression (48.8%; PHQ-9 scores ≥ 10), and more than a quarter of participants showed clinical levels of posttraumatic stress (27.3%; PCL-5 scores ≥ 31). Latinxs reported on average 22 types of negative pandemic life impacts on the Epidemic-Pandemic Impacts Inventory. Endorsement of mental health symptoms, severity of COVID-19 fears, and COVID-related life impacts varied based on several demographic characteristics including gender, marital status, educational attainment, employment, income, insurance coverage, vulnerability to COVID-19, and essential worker status. Discussion: Overall, the cross-sectional results of this study revealed that RGV Latinx residents experienced high levels of psychological distress during the pandemic. Results suggest that Latinx women were most affected by the psychological consequences of the pandemic. More research is needed with communities living near the U.S.-Mexico border as they may be particularly vulnerable to mental health problems during the pandemic. Clinical implications include outreach efforts may be targeted to certain populations.